2019
DOI: 10.1215/00127094-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Curvature estimates for constant mean curvature surfaces

Abstract: We derive extrinsic curvature estimates for compact disks embedded in R 3 with nonzero constant mean curvature.Mathematics Subject Classification: Primary 53A10, Secondary 49Q05, 53C42

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Thus, L 1 is a limit leaf of L 1 . As L 1 is a regular lamination of R 3 − S, then the stable limit leaf theorem [26,27] applies in this case and gives that the two-sided cover of L 1 is stable. Since the set Lim(L 1 ) of limit leaves of L 1 forms a sublamination (closeness of Lim(L 1 ) follows essentially from taking double limits), then the first sentence of item 2 of Theorem 1.4 reduces to checking that L(L 1 ) is a plane.…”
Section: Example 23 Colding and Minicozzimentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, L 1 is a limit leaf of L 1 . As L 1 is a regular lamination of R 3 − S, then the stable limit leaf theorem [26,27] applies in this case and gives that the two-sided cover of L 1 is stable. Since the set Lim(L 1 ) of limit leaves of L 1 forms a sublamination (closeness of Lim(L 1 ) follows essentially from taking double limits), then the first sentence of item 2 of Theorem 1.4 reduces to checking that L(L 1 ) is a plane.…”
Section: Example 23 Colding and Minicozzimentioning
confidence: 97%
“…The paper is organized as follows. In Section 2 we give examples of singular minimal laminations and obtain some results to be used in the proof of the main Theorem 1.4; these auxiliary results are based on the local removable singularity theorem [31] and the stable limit leaf theorem for the limit leaves of a minimal lamination [26,27]. In Section 3 we prove Theorem 1.4.…”
Section: Conjecture 15 (Fundamental Singularity Conjecture)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the proof of this result, Meeks and Rosenberg [15] showed that complete, connected minimal surfaces with positive injectivity radius embedded in R 3 are proper. Meeks and Tinaglia [16] then extended both results by proving that complete surfaces with constant mean curvature embedded in R 3 are proper if they have finite topology or positive injectivity radius. It is natural to ask to what extent similar properness results hold for complete surfaces of finite topology in other ambient spaces, where the surfaces are not necessarily embedded or have constant mean curvature.…”
mentioning
confidence: 95%
“…|A M | denotes the norm of the second fundamental form of M .3. The radius of a Riemannian n-manifold with boundary is the supremum of the intrinsic distances of points in the manifold to its boundary.The next two results are contained in [20], see also [18,19,21,22,23].Theorem 2.2 (Radius Estimates) There exists an R ≥ π such that any H-disk in R 3 has radius less than R/H.…”
mentioning
confidence: 99%